Formação artística: tensões entre aprendizado informal e abordagens escolares - Sergio Roberto Vaz Ferrerira (2014)
This research investigated the practice of reading images of art by 17 students of the 3rd cycle of basic education in a public school in the city of Count, Minas Gerais. This study assessed the relationship between design students about art, its baggage of artistic knowledge acquired informally and teaching of art in this particular school. To this end, in addition to theoretical research, a semistructured interview with each subject was performed, followed by two free assessment reproductions of works of art and the production of a drawing attached to the subject of the interview. Through the data collected during this process, we sought to infer the view of respondents on Art, artist and artwork. In parallel, a mapping of school space, as well as the contents treated in school art classes and how the school community was the art - whether as curriculum content or as something in the culture of the community that houses the school and its students. The perspective of the researcher - the look launched on the study context - was set from the concept of 'experience near' and 'far' experience of Geertz (2008). The study of narratives derived from interviews and produced drawings, analysis of data collected in the field research and its implications for teaching and learning in art school relied on the conceptions of Aguirre (1996, 2007, 2008a, 2008b) on education of Art. The definition of the role of art in school was supported by the contributions of Dewey (1980), Rorty (1989), Efland (2003) and Barbosa (1988, 1990, 2002, 2003, 2005, 2008), which, at different times of education and society, represented new horizons for teaching art. The concept of narrative that, for Aguirre, happens when the student talks about his experience with the work / image found justification in the texts on the figure of the narrator, Benjamin (1994) and the construction of speech acts Bakhtin (2000). Permeated all discussions and considerations Berger's (1972) theories on the relationship between individual and image aspects of enjoyment in Didi- Huberman (2013) and the definition of modernity Bauman (2001) and Parsons (1974). This investigation is configured as a case study, by definition, qualitative, which aims to be a reference and reflection for future researchers studied the theories and practices and the discussion about a curriculum for teaching art to devise the diversity and fluidity of contemporary society and culture by relaxing driving experience and recognizing your audience as the central focus of the educational process, anchored in the reflections on the Curriculum Narrative Goodson (2007).